FUNGSIONALISASI UNDANG-UNDANG NOMOR 1 / PNPS TAHUN 1965 DAN PASAL 156a KUHP TERHADAP TINDAK PIDANA PENISTAAN AGAMA DI INDONESIA - IKHSAN '; Erdianto ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Criminal acts of defamation of religion stipulated in Article 156 and 156a of the Criminal Code, which criminalize whoever intentionally publicly issued a feeling or does something which is fundamentally hostility, abuse or desecration of a religion followed in Indonesia with the intention that that person no religion anything that Belief in God Almighty.Criminal acts of defamation of religion provided for in Article 156 of the Criminal Code, is one of the